2020
DOI: 10.20473/jbe.v8i12020.42-49
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Access of Drinking Water and Sanitation With Diarrhea Incidence in East Java

Abstract: Background: Diarrhea is still a major health problem in Indonesia. The Province of East Java ranks the second-highest number of diarrhea incidence after West Java, which reached 1,048,885 patients. The most dominant factors contributing to diarrheal diseases are water and family latrines. Purpose: This study aims to analyze the relationship between access to drinking water and proper sanitation with the incidence of diarrhea in East Java. Methods: This study was an observational study with a correlation study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Another environmental health factor that affect diarrhea were the availability of healthy latrines. Research conducted in several regions of Indonesia showed that there was a relationship between the availability of healthy latrines and diarrhea for children under five years old (14,23,27). Improper faeces management and unhealthy latrines will increase the risk of diarrhea (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another environmental health factor that affect diarrhea were the availability of healthy latrines. Research conducted in several regions of Indonesia showed that there was a relationship between the availability of healthy latrines and diarrhea for children under five years old (14,23,27). Improper faeces management and unhealthy latrines will increase the risk of diarrhea (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in several regions of Indonesia showed that there was a relationship between the availability of healthy latrines and diarrhea for children under five years old (14,23,27). Improper faeces management and unhealthy latrines will increase the risk of diarrhea (27)(28)(29). This is because many infectious diseases are transmitted by fecal-oral transmission and through various media (such as water and soil), direct contact with surface of contaminated objects, or through vector (such as flies) when disposing of feces anywhere (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lighting factor, including the other physical house parameters like temperature and humidity, does not relate to the incidence of diarrhea in under-five children, according to a study in Muna Barat Regency (27). However, a secondary data-based study in 5 cities in East Java mentions that lighting is also the one component required for a healthy latrine (28). Adequate lighting is considered a single requirement for a sanitary latrine to avoid insects or bacteria contaminating the water.…”
Section: Discussionmentioning
confidence: 99%
“…The main source of drinking water, washing hands before taking water from storage containers, domestic waste disposal sites, and soap for washing hands were the most important factors for the prevention of diarrhea in children (Soboksa et al, 2020). Likewise, previous research also showed a relationship between access to drinking water and inadequate sanitation with the incidence of diarrhea found in East Java (Prakoso, 2020).…”
Section: Introductionmentioning
confidence: 87%